IMPLEMENTASI ILMU AL–MUNASABAH DALAM MEMAHAMI AYAT-AAYAT HUKUM EKONOMI SYARIAH - Nandang Ihwanudin; Aliya Putri Fitria Nuryanti; Alya Syifa Utami Handriansyah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2021)
This study aims to find out and analyze verses related to sharia economic law by implementing the science of al-munasabah which is a branch of the ulumul Quran. This knowledge can help and open one's mind to be able to understand the various rules and laws contained in the Qur'an. The research approach used is qualitative research with literature studies and content analysis of verses that are strongly suspected of being categorized as containing sharia economic law. After analyzing, by implementing Ilm al-Munasabah it was found that: (1) The foundations on which Sharia Economic Law was built include QS. 6: 165 which is correlated with the previous verse (164) and after it (166) shows that the freedom to utilize the potential of natural resources is followed by the obligation to account for the giver of the gift as a manifestation of the principle of monotheism; (2) refers to the interpretation of the QS. 2: 168, 5: 8, and 16: 91, the principles of sharia economic law are found as follows: (a) The principle of meeting each other's needs properly and correctly, (b) helping each other in goodness, (c) mutual benefit, (d) compete positively with each other, (e) protect and provide mutual guarantees, (f) maintain justice and balance, (g) fulfill each other's promises, and (h) do not harm or harm each other; and (3) based on QS 4: 160, 161, 162; 3: 130; 2: 175-179, it was found that the practice of usury arose as a result of the philanthropic Islamic economic institutions that did not work. Therefore, Allah swt with pris al-tadaruj fi al-hukm, criticizes the practice of usury, then double usury is forbidden, and next, all forms of usury are forbidden